A qualitative analysis of the experience of being LGBTQ in graduate school - Sokolowski, Elizabeth, author; Chavez, Ernest, advisor; Rickard, Kathryn, committee member; Carlson, Laurie, committee member; Davalos, Deana, committee member (Colorado State University. Libraries, 2020)
The current study sought to understand LGBTQ campus climate for LGBTQ doctoral students. Narrative analysis was used during this exploratory study to identify "when" the three LGBTQ doctoral student participants had experiences related to their LGBTQ identities, including "what" was happening during those events and "how" it was happening. These experiences occurred during six events (i.e., applying to graduate programs, receiving letter of acceptance from graduate program, visiting weekend after receiving acceptance letter, choosing advisor or research lab, working as a graduate teaching assistance, and preparing for PhD candidacy exams) and four time periods (i.e., early general experiences in the graduate program, general graduate school experiences, general research lab experiences, and general social experiences during graduate school). This study also identified how these experiences supported or hindered LGBTQ doctoral student success. Overall, the results suggested that LGBTQ doctoral students expended substantial effort to manage the harmful components of campus climate, which were present across locations, times, and roles as a doctoral student. Finally, participants shared their own proposed changes to improve campus climate, and the primary researcher provided an overarching list of recommendations to improve LGBTQ campus climate for LGBTQ doctoral students.
Keywords: campus climate; graduate students; microaggressions; doctoral students; attrition; LGBTQ